Hadith #1903 - Sunan Ibn Majah - al-'Ala' bin al-Hadrami; Atab bin Ziyad al-Khrasany عتاب بن زياد الخراساني أبو عمرو المروزي; Hyan al-A'rj حيان الأعرج; Muhammad bin Maymun, Abu Hamza محمد بن ميمون المروزي أبو حمزة السكري; Muhammad bin Zayd bin 'Abdullah محمد بن زيد بن عبد الله بن عمر (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade two kinds of transactions: Mulimasah and Mundbadhah.
Grade: